A COMPREHENSIVE REVIEW ON MICROPROPAGATION OF BACOPA MONNIERI L. - Surbhi Bhalerao; Avinash Jondhale; Smita Chava; Sagar Bhagwat; Bharat Magar; Nisha Suryawanshi (The Bioscan, 2025)
Bacopa monnieri L. Pennell, is an important medicinal plant and is commonly known as Neer-brahmi that belongs to the family Scrophulariaceae. Bacopa is growing through vegetative propagation in nature. Bacopa is a well-known drug in Ayurveda and contain a variety of chemical compounds that can be used as medicines. It is used for increases intelligence & improves memory. Brahmi is also used for antioxidant, anti-inflammatory and anti-hepatotoxic activites. Presently, Bacopa raw materials huge demand in the market, particularly in medicinal industries. But, naturally propagation of Bacopa not sufficient to provided commercial demand. So, to overcome this problem resolved through by using micropropagation techniques to sufficient for the production of important secondary metabolites. Microprogation is useful for rapid propagation and conservation of medicinally important plants with increased production of bioactive compounds. Now this review article, we study and observed for the combination of on MS medium with auxin and cytokine (BAP, IAA, IBA, NAA, Kinetin, 2,4-D) for callus, shoot and root formation for cultivation of better propagation of Bacopa monnieri.